Analysis of three phase controlled rectifier with the same distance control as compared to the same angle control - S., Sudirman; A., Sri Kurniati (UI Scholars Hub, 2007)
Analysis of three phase controlled rectifier with the same distance control as compared to the same angle control. This research aim to compare the firing of the same distance and the same angle control at three phase controlled rectifier with seen generated harmonic at input (AC side). Then calculate of rectifier efficiency and power factor comparison from both the control type. The rectifier use passive filter with resistance 11 ohm and is analysed with program simulation using PSPICE version 7.1. Result of research indicate that use of the same distance control generates the 5th and 7th harmonics, while the same angle control generates the 3rd , 5th and 7th harmonics at the input (AC side). At the output (DC side), the same distance control type generates the 6th voltage ripples, while the same angle control generates the 2nd, and 6th voltage ripples. The result of calculation of voltage ripples that happened equal to 3.5% with efficiency 99.8% at same distance control, while at the same angle control obtained voltage ripples equal to 4% with efficiency 99.7% . At the firing angle 300 obtained by THD input equal to 50.26% with power factor equal to 0.89 at same distance control type, while the same angle control obtained by THD input equal to 53,831% with power factor to 0,87. From this result indicate that the firing of thyristor with the same distance better then is the same angle control.